A kind of ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization and its preparation method
Patent Information
- Application Number
- CN202611151892.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-31
AI Technical Summary
现有的常规物理掺杂或硅质填充技术无法从底层逻辑上解决晶相粗化与晶格解聚的双重衰退机制
[0017]在此基础上,本发明的稳定剂在微观晶体结构中实现了多种杂原子特定位点的精准取代与嵌入。特定的原子不仅增加了硅酸盐化学键的断裂活化能,中和了电荷缺陷并降低了晶格膨胀应力,还在多面体层间构筑了刚性的微观交联结构。这种结构对抗了高温热激化引发的相变滑移与位错运动,通过强大的微观牵制作用将相变失稳温度推迟至更高温区,从原子级别切断了硅酸盐双链在超高温下的解聚路径,赋予了晶相材料在长期极端温压环境中的结构恒定性。通过特定的络合控速联合限域水热工艺,本发明方案解决了多种前驱体水解速率差异过大的技术壁垒,消除了副相沉淀,提高了产物的晶化纯度和转化收率,同时大幅缩短了晶化周期,展现出优异的工业化应用前景。
Smart Images

Figure CN122647140B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oil and gas well cementing engineering technology, and in particular to an ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization and its preparation method. Background Technology
[0002] As global energy strategies increasingly expand towards deep, ultra-deep, and unconventional oil and gas resources, the operating environment at the bottom of wells is becoming more extreme. In cementing projects for ultra-high-temperature deep wells where the static temperature at the bottom of the well exceeds 200°C, or even reaches 240°C to 260°C, the amorphous calcium silicate hydrate (CSH gel), the main product of conventional oil well cement hydration, undergoes dehydration in environments exceeding 110°C and transforms into a high-density, high-crystallinity phase. This leads to a sharp increase in cement stone porosity and permeability, and a precipitous drop in compressive strength. Currently, the industry typically incorporates siliceous materials into the cement formulation to alter the evolution path of the hydration products, generating silica-rich crystalline phases such as hard calcium silicate with lower permeability and higher inherent mechanical strength, thereby maintaining structural integrity in the short term.
[0003] However, under harsh conditions such as 240 ℃ and ultra-high pressure, traditional sand-added silicate cement still experiences irreversible and severe late-stage strength degradation during long-term service. The root cause of this phenomenon lies in the instability of deep thermodynamics and microstructure evolution mechanisms: On the one hand, the initially formed hard silicate crystals face interfacial energy instability. To minimize the overall specific surface area energy, the system promotes the spontaneous dissolution and redeposition of thermodynamically metastable nanocrystals onto the surface of larger crystals. This long-term Oswald ripening effect leads to uncontrolled coarsening evolution of the crystals, destroying the original dense interwoven hydration network, triggering the initiation of numerous microcracks and loss of matrix density. On the other hand, under extreme thermodynamic conditions, the depolymerization pathway of silicate double chains is activated at high temperatures. The silicon-oxygen tetrahedral units constituting the double chains possess high internal energy and are highly susceptible to spontaneous chemical bond breakage and depolymerization due to thermal excitation. This localized lattice depolymerization and phase transition instability further weakens the intrinsic tensile and shear strength of the crystals, inducing micro-region topological phase transitions, leading to a collapse in macroscopic mechanical strength. Existing conventional physical doping or silicon filling techniques cannot fundamentally solve the dual decay mechanism of crystal phase coarsening and lattice deagglomeration. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides an ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization and its preparation method.
[0005] According to one aspect of the present invention, an ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization is provided, wherein the stabilizer comprises mesoporous nano-hard silicate calcium stone seed crystals co-doped with aluminum, phosphorus, and titanium. The role of introducing these mesoporous nano-hard silicate calcium stone seed crystals is that their large surface area, highly matched crystal structure, and extremely low crystallization barrier enable them to instantly become highly efficient heterogeneous nucleation seeds in the early stages of deep well cementing. A large amount of free components in a supersaturated state are adsorbed by the active interface of the seed crystals, and within a very narrow time window, they collectively accrete and deplete the nutrients at an extremely high rate, ensuring that no single crystal in the system can grow into a coarse agglomerate through the Oswald ripening effect, thereby permanently freezing the microstructure of the cement stone within a dense, nano-interwoven three-dimensional network.
[0006] Preferably, in the stabilizer, the molar ratio of phosphorus to aluminum is 0.5; the total molar ratio of calcium to the framework elements silicon, aluminum, titanium, and phosphorus is 0.85 to 0.90. The reason for limiting the molar ratio of phosphorus to aluminum to 0.5 is that when aluminum atoms replace silicon atoms, each aluminum atom generates one unit of negative charge defect, while each phosphorus atom entering the framework provides one unit of positive charge. Introducing phosphorus at a ratio of 0.5 can partially compensate for the negative charge defects introduced by aluminum. The remaining negative charge not compensated by phosphorus is balanced by protonated hydroxyl groups and calcium ions in the system, and the three together constitute a local charge balance network. At the same time, the embedding of smaller-radius phosphorus atoms can also compensate for the lattice expansion stress caused by aluminum substitution. The inventors have found that when the phosphorus-aluminum molar ratio is maintained at around 0.5, the overall balance between charge compensation and lattice strain compensation is optimal: if the phosphorus ratio is too low, the negative charge and expansion stress induced by aluminum cannot be effectively alleviated; if the phosphorus ratio is too high, or even close to 1, excess phosphorus cannot fully enter the framework, easily leading to the precipitation of phosphate impurities and interfering with the orderly development of double chains. Maintaining the molar ratio of calcium to total framework elements in the system within the range of 0.85 to 0.90 is to create a microscopic thermodynamic environment rich in silicon and poor in calcium. This ratio can macroscopically force the repulsion of the formation of secondary phases such as siliceous calcium silicate and drive the structure to develop into directional hard siliceous calcium silicate with extremely high purity.
[0007] More preferably, in the microcrystalline structure of the stabilizer, aluminum atoms replace silicon atoms in the silicon-oxygen tetrahedral framework, phosphorus atoms are embedded in the silicon-oxygen tetrahedral framework to partially compensate for the negative charge vacancies of the aluminum atoms, and titanium atoms are mainly located in the interlayer interlayers of the calcium-oxygen polyhedral layers of the hard silicate. The successful displacement of silicon atom positions by aluminum atoms induces the formation of a transition state with higher energy buffering capacity, significantly increasing the critical activation energy required for the tensile breakage of adjacent chemical bonds. The simultaneous embedding of phosphorus atoms partially neutralizes the negative electric field defects of the former and releases the lattice distortion stress, further suppressing the high-temperature depolymerization pathway of the double-chain structure. Due to their high bonding energy, titanium atoms mainly act as rigid rivets in the interlayer interlayers, resisting the large-scale relative dislocation sliding of atomic layers caused by high temperatures, thereby raising the temperature critical point for phase transformation instability of the hard silicate.
[0008] According to another aspect of the present invention, a method for preparing the above-mentioned ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization is provided, comprising the following steps: S1, dispersing an aluminum source and a titanium source in an organic solvent, adding a complexing agent to perform a chelation reaction, obtaining a precursor solution A; S2, dispersing a silicon source and a phosphorus source in an organic solvent, adding water and an acid regulator to perform a hydrolysis-condensation reaction, obtaining a silicon-phosphorus cocondensation sol B; S3, dissolving a calcium source in water, adding a block copolymer template agent, and mixing to obtain a micelle solution C; S4, adding the precursor solution A to the silicon-phosphorus cocondensation sol B and mixing to obtain a composite homogeneous sol, subsequently... The composite homogeneous sol is injected into the micelle solution C, and an alkaline regulator is added to adjust the pH value of the mixture. After closed aging, a gel slurry is obtained. S5: The gel slurry is subjected to a desolvation treatment to remove the organic solvents and alcohols released by the hydrolysis of the precursor, and water is added to redisperse it to obtain an aqueous gel slurry with water as the main liquid medium. S6: The aqueous gel slurry is placed in a closed reactor for hydrothermal crystallization reaction. S7: After the hydrothermal crystallization reaction is completed, the product is separated, washed, solvent replaced, and dried to obtain the ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization.
[0009] Preferably, in step S1, the organic solvent is anhydrous ethanol, the aluminum source is aluminum isopropoxide, and the titanium source is tetrabutyl titanate; the complexing agent is acetylacetone; and the ratio of the molar number of the complexing agent to the sum of the molar numbers of titanium atoms in the titanium source and aluminum atoms in the aluminum source is 2.2:1. Transition metal precursors such as tetrabutyl titanate and aluminum isopropoxide hydrolyze extremely rapidly, and direct use can lead to spontaneous phase separation and precipitation. Acetylacetone, as a rate-regulating complexing agent, chelates with the metal center in the system, constructing a high-density steric barrier layer. This molar ratio of 2.2:1 ensures that highly active metal sites are fully coated, slowing down the water molecule substitution rate and significantly reducing the hydrolysis rate of the transition metal precursor, thus harmonizing its hydrolysis and polycondensation with that of the silicon-based precursor, providing conditions for subsequent co-condensation. If the molar ratio is too low, the shielding effect will be poor, and precipitation separation will still occur; if the ratio is too high, excessive residual complexing agent will interfere with the subsequent copolymerization and gelation process.
[0010] More preferably, in step S2, the silicon source is tetraethyl orthosilicate, and the phosphorus source is triethyl phosphate; in the hydrolysis-condensation reaction, the molar ratio of water to tetraethyl orthosilicate is 4.5:1; the acid regulator is nitric acid, and the addition of the acid regulator controls the pH of the reaction system to be between 2.5 and 3.0. Limiting the water-to-tetraethyl orthosilicate ratio to 4.5:1 provides an appropriate hydrolysis driving force, ensuring that tetraethyl orthosilicate is fully hydrolyzed while avoiding premature gel aggregation caused by excessive water. Stabilizing the pH of the system at 2.5 to 3.0 with nitric acid allows the silicon condensation reaction to be in a controlled kinetic state. It should be noted that the hydrolysis of triethyl phosphate under the weakly acidic conditions at room temperature is relatively slow. During this stage, a transparent homogeneous sol is mainly formed, consisting of silicon-oxygen oligomers with phosphorus source uniformly dispersed at the molecular level. This creates uniform preconditions for phosphorus to enter the silicon-oxygen framework in the subsequent high-temperature hydrothermal stage. The substantial intercalation of phosphorus into the silicon-oxygen tetrahedral framework and the formation of inter-silicon-phosphorus bridging oxygen bonds are mainly completed during the 220 °C hydrothermal crystallization stage.
[0011] Further, in step S3, the calcium source is calcium nitrate tetrahydrate, and the block copolymer template agent is Pluronic F127. The preparation process of the micelle solution C includes heating the mixture to 45 °C and continuously stirring until the block copolymer template agent is completely dispersed to obtain a homogeneous micelle solution. Pluronic F127 polymeric block copolymer is used as the template agent and treated at 45 °C because this temperature is higher than its critical micelle temperature. The hydrophobic segments of polypropylene oxide dehydrate, while the hydrophilic segments of polyethylene oxide remain extended, thus self-assembling to form a large number of micelles. These micelles, acting as soft templates, occupy space during crystal growth and leave pores in the product, giving the product a mesoporous structure. Simultaneously, calcareous silica itself has an inherent growth habit of preferentially growing into needle-like or fibrous crystals along its bichain direction. Under the dispersion and interfacial regulation of the micelle soft template, this anisotropic growth habit is strengthened, thereby guiding the product to develop into a high aspect ratio mesoporous nanofiber structure. It should be noted that the relatively dilute F127 micelle solution used in this invention forms an isotropically dispersed micelle system, which serves to provide mesopores and interface regulation, rather than relying on high concentrations to form a long-range ordered liquid crystal phase.
[0012] Further, in step S4, the alkaline regulator is an aqueous solution of tetramethylammonium hydroxide; the alkaline regulator is added to adjust the pH of the mixed system to be constant between 11.5 and 11.8; the sealed aging time is 12 h. Tetramethylammonium hydroxide can provide a strong alkaline mineralizer without introducing conventional sodium and potassium alkali metal ion impurities into the system. Anchoring the endpoint pH value to 11.5 to 11.8 is extremely critical: this pH range perfectly matches the core region of the thermodynamic phase diagram for the formation of the hard silicate double-chain structure; if the pH value is below 11.5, the crystallization kinetics will be deflected, resulting in the formation of a large amount of byproduct calcium silicate phase; if the pH value is above 11.8, especially above 12.5, it is very easy to induce a large amount of spontaneous precipitation of amorphous calcium carbonate, and strong alkali will destroy the micelle micro-confinence of the organic soft template.
[0013] Further, in step S5, the removal process is preferably performed by vacuum distillation of the gel slurry at 55°C to 65°C. Given that the aged slurry contains anhydrous ethanol introduced by the precursor and sol, as well as alcohols released from precursor hydrolysis, these low-boiling-point alcohols will generate vapor pressures far exceeding those of water in a high-temperature, closed hydrothermal environment. If not removed beforehand, the total pressure of the system at the hydrothermal temperature will significantly exceed the saturated vapor pressure of pure water, not only deviating from the set pressure window but also posing a safety hazard of overpressure in the reactor. By removing most of the alcohols by vacuum distillation at the above temperature before loading into the reactor, and by adding deionized water to re-slurry and disperse the material, the slurry entering the reactor uses water as the main liquid phase medium. This ensures that subsequent hydrothermal crystallization occurs under controllable and safe autogenous pressure, without altering the already assembled silicon-calcium framework and template structure within the gel.
[0014] More preferably, in step S6, the filling degree of the aqueous gel slurry in the sealed reactor is controlled between 65% and 70%; the initial heating rate of the hydrothermal crystallization reaction is 1.5 ℃ / min, the target hydrothermal temperature is 220 ℃, and the isothermal crystallization time at 220 ℃ is 16 h. Controlling the filling degree to 65% to 70% ensures that an appropriate gas phase space is maintained within the reactor. This guarantees the presence of a free vapor phase above the liquid slurry, avoiding the risk of overpressure due to thermal expansion of the liquid in a full-liquid state, while also preventing excessive gas phase space from causing a large amount of water to escape from the liquid phase in gaseous form and altering the effective liquid-solid ratio of the slurry. Since the slurry in the reactor is predominantly aqueous after the previous alcohol removal treatment, the pressure at 220 ℃ when gas-liquid equilibrium is reached is mainly determined by the saturated vapor pressure of water at that temperature, approximately 2.3 MPa to 2.5 MPa, thus forming a stable high-temperature self-generated pressure environment. A heating rate of 1.5 ℃ / min ensured that the gel matrix underwent a uniform and gradual thermal field nucleation stage. Combined with the interfacial enrichment effect of the organic template agent, maintaining hydrothermal conditions at 220 ℃ for 16 h significantly reduced the hydrothermal diffusion barrier required for in-situ reprecipitation, thus significantly shortening the crystallization process that typically takes tens of hours. If the temperature is below 220 ℃ or the time is insufficient, it may result in more amorphous residues and immature development of mesoporous crystals.
[0015] Most preferably, in step S7, the washing includes ultrasonic washing with deionized water at 80 °C at least three times; the solvent replacement is deep solvent replacement using anhydrous ethanol; and the drying treatment is continuous devastation drying for 12 h under conditions of absolute pressure less than 0.01 MPa and temperature of 105 °C. It should be noted that after the 220 °C strongly alkaline hydrothermal treatment, the block copolymer template agent itself has undergone significant pyrolysis and chain segment degradation, and its residues mainly exist in the form of small molecule fragments and ions; the physical energy of the 80 °C thermal field combined with ultrasound is mainly used to open the aggregation interface, desorb and flush out the free acid radicals, unreacted ions and the aforementioned degradation fragments remaining in the mesopores. Considering the characteristics of poly(ethylene oxide)-poly(propylene oxide) block copolymers, such as the dehydration and easy aggregation of hydrophilic segments in high-temperature aqueous phases, simple water washing cannot remove the complete polymer through dissolution. Therefore, this invention employs deep replacement with anhydrous ethanol. Ethanol has excellent dissolving power for this type of copolymer, thoroughly extracting and removing stubborn organic residues adsorbed on the pore walls. Simultaneously, its low surface tension can replace water within the mesopores. Since water molecules have high capillary surface tension, direct dehydration and drying of water-containing materials can lead to irreversible collapse of the flexible mesoporous structure and severe hard agglomeration of the powder due to the shrinkage stress generated during water escape. Introducing anhydrous ethanol replacement protects the fragile newly formed mesoporous network, resulting in a highly fluffy, high-specific-surface-area ultrafine powder that meets the process requirements for rapid dispersion in engineering settings.
[0016] This invention relates to a crystal phase-stabilized ultra-high temperature cement stone strength stabilizer and its preparation method. Through multi-element co-doping synergy and pre-phase induction control, it fundamentally blocks the long-term strength degradation problem under ultra-high temperature conditions. This stabilizer, acting as a heterogeneous nucleation center, is pre-distributed uniformly in the cement matrix. Through an extremely low crystallization barrier, it instantaneously adsorbs supersaturated free ions, explosively guiding the generation of a large number of fine, interwoven nanocrystals with high aspect ratios and high surface energy. Because the simultaneous growth of massive crystals depletes the reactive materials within the system, it effectively blocks the path of any single crystal engulfing its kind to grow into a coarse crystal, thereby eliminating the risk of crystal coarsening and loss of matrix density. It also constructs a three-dimensional interpenetrating dense network, significantly reducing the porosity and water permeability of the cement stone and enhancing its fluid containment capabilities.
[0017] Based on this, the stabilizer of this invention achieves precise substitution and embedding of various heteroatoms at specific sites within the microcrystalline structure. These specific atoms not only increase the activation energy for breaking silicate chemical bonds, neutralize charge defects, and reduce lattice expansion stress, but also construct a rigid micro-crosslinked structure between polyhedral layers. This structure counteracts phase transition slip and dislocation movement induced by high-temperature thermal excitation, delaying the phase transition instability temperature to an even higher temperature region through a strong micro-binding effect. It atomically severs the depolymerization path of silicate double chains at ultra-high temperatures, endowing the crystalline material with structural stability under long-term extreme temperature and pressure environments. Through a specific complexation-controlled rate-controlled combined confined hydrothermal process, this invention overcomes the technical barrier of excessively large differences in the hydrolysis rates of various precursors, eliminates secondary phase precipitation, improves the crystallization purity and conversion yield of the product, and significantly shortens the crystallization cycle, demonstrating excellent prospects for industrial application. Attached Figure Description
[0018] Figure 1 This is a comparison of the X-ray powder diffraction (XRD) patterns of the strength stabilizer powder of the present invention, showing the diffraction patterns of the representative example sample and the comparative sample, used to characterize the phase composition of each strength stabilizer and the phase purity of the target hard silica-calcium phase; the horizontal axis in the figure is the diffraction angle 2θ, and the vertical axis is the diffraction intensity.
[0019] Figure 2 The image shown is a field emission scanning electron microscope (SEM) image of the strength stabilizer (S1) obtained in Example 1 of the present invention, which is used to show the microstructure, whisker morphology and interwoven network structure of the strength stabilizer.
[0020] Figure 3 The variable-temperature in-situ X-ray diffraction patterns of the strength stabilizers obtained in Example 1 (S1) and Comparative Example 1 (D1) of this invention are used to compare and characterize the phase transition initiation temperature of the two phases during the programmed temperature rise process, from the hard silica-calcium phase to the high-temperature phases such as wollastonite; the horizontal axis in the figure is the diffraction angle 2θ, and the vertical axis is the diffraction intensity at different temperatures. Detailed Implementation
[0021] The present invention will be further described in detail below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto. Unless otherwise specified, the raw materials used in the following embodiments are all commercially available analytical grade reagents. Among them, various liquid metal alkoxide precursors have high hydrolysis sensitivity, and are operated in a dry and inert atmosphere during weighing, transfer and storage to avoid the precursors from premature hydrolysis and inactivation caused by ambient moisture, which would affect the homogeneity and reproducibility of the final product.
[0022] The ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization provided by this invention is centered on a mesoporous nano-hard silicate calcium stone seed crystal co-doped with aluminum, phosphorus, and titanium. From a materials chemistry perspective, this seed crystal uses a hard silicate calcium stone framework consisting of infinitely extended silicon-oxygen tetrahedral double chains and alternating layers of calcium-oxygen polyhedra as its basic skeleton, and introduces three heteroatoms with distinct properties and complementary functions within this framework. Aluminum atoms enter the silicon-oxygen tetrahedral network in a trivalent state, equally crowding out the lattice sites of tetravalent silicon atoms. Due to the decrease in valence, each aluminum site generates a unit of negative charge defect. In the high-temperature hydrothermal system rich in hydroxyl groups, this defect spontaneously captures additional hydroxyl groups through the principle of energy minimization, forming a five-coordinate hydroxylated transition state with high energy buffering capacity. This significantly increases the critical activation energy required for the tensile breakage of adjacent silicon-oxygen bonds, thus delaying or even blocking the depolymerization process of silicate double chains at ultra-high temperatures from the molecular bond energy level. However, simply introducing a large number of aluminum atoms can lead to considerable internal distortion stress in the lattice due to tetrahedral volume mismatch. Furthermore, the resulting negative charge defects, if not properly managed, can weaken lattice stability. Therefore, this invention simultaneously embeds smaller pentavalent phosphorus atoms. Each phosphorus atom provides a unit of positive charge when replacing the central silicon site of an adjacent tetrahedron. It should be noted that this invention sets the phosphorus-aluminum molar ratio to 0.5, meaning that the phosphorus entering the framework provides partial, not full, charge compensation for the negative charge defects introduced by aluminum. The remaining negative charge not offset by phosphorus is balanced by protonated hydroxyl groups and calcium ions in the system, forming a stable local charge balance network. Experiments have confirmed that at this ratio, the hard silica-calcium lattice maintains good electroneutrality and structural order, without any deterioration in phase purity due to charge imbalance. Simultaneously, the polarity complementarity between phosphorus and aluminum atoms in their bond lengths relaxes and releases the lattice expansion stress induced by aluminum doping, allowing the entire doped framework to return to a stable configuration on the energy potential surface. This comprehensive balance between charge and stress is the fundamental reason for choosing a phosphorus-aluminum molar ratio of around 0.5: when the phosphorus ratio is too low, the negative charge and expansion stress induced by aluminum cannot be effectively alleviated; while when the phosphorus ratio is too high, even close to 1, the excess phosphorus cannot fully enter the framework and is prone to precipitate as a phosphate impurity phase, interfering with the orderly development of the double chains. Unlike the synergistic effect of aluminum and phosphorus on the silicon-oxygen chain framework, the target of titanium atoms is the interlayer gaps and lattice defect interfaces of the calcium-oxygen polyhedral layer in hard silica-calcium silicate. Due to the high bond energy of the titanium-oxygen bond, tetravalent titanium ions are guided to deposit between parallel polyhedral layers and at defect sites under the complexation rate control and confined hydrothermal conditions of this invention, mainly existing in the form of interlayer rigid rivets. When the external temperature rises to 240 °C or even higher, and the framework structure undergoes strong thermal contraction and attempts to undergo phase transformation collapse through grain boundary slip and dislocation movement, these titanium nodes exert a strong pinning and restraining effect on the relative slip path of the large-scale atomic layers, thereby delaying the temperature critical point of phase transformation instability of hard silica-calcium silicate to a higher temperature region.The three heteroatoms each perform their own functions while complementing each other, jointly constructing a dual chemical defense barrier at the atomic scale against crystal phase coarsening and lattice deagglomeration.
[0023] Regarding the component ratio, this invention specifies the key molar ratio within the doped system. The molar ratio of phosphorus to aluminum is controlled at 0.5. This ratio balances the dual requirements of charge compensation and lattice strain compensation: phosphorus entering the framework partially compensates for the negative charge defects introduced by aluminum, and the remaining negative charge is balanced by protonated hydroxyl groups and calcium ions, maintaining local electroneutrality; simultaneously, the smaller radius of phosphorus effectively relaxes the lattice expansion stress caused by aluminum substitution. The inventors discovered in experiments that both excessively high and low ratios disrupt this overall balance: when phosphorus content is too low, the negative charge and expansion stress induced by aluminum are not adequately alleviated, and the residual charge unevenness and distortion stress in the lattice become weak points at high temperatures; when phosphorus content is too high, even approaching equimolarity, excess phosphorus is difficult to fully enter the framework and easily precipitates as a phosphate impurity phase, which interferes with the orderly development of double strands and reduces the purity of the target phase. Correspondingly, the molar ratio of calcium to the total amount of the four framework elements (silicon, aluminum, titanium, and phosphorus) in the system is limited to between 0.85 and 0.90, deliberately creating a microscopic stoichiometric environment that is rich in silicon and poor in calcium. From the thermodynamic phase diagram of the hydrothermal formation of calcareous silicate, a high calcium-to-silicon ratio drives the system to evolve towards calcium-rich secondary phases such as calcareous silicate and calcium metasilicate. However, when the ratio of calcium to the total amount of the framework is controlled below 0.90, and calcium is depleted to a certain extent, the system is thermodynamically forced to reject the nucleation of the above-mentioned secondary phases, and instead develops directionally along the path of highly pure silicon-rich calcareous silicate.
[0024] The strength stabilizer described in this invention is prepared according to a general process route of complex-controlled rapid-release sol-gel combined confined hydrothermal crystallization. The complete process encompasses six steps: preparation of titanium-aluminum coordination precursor solution, preparation of silicon-phosphorus co-condensation sol, construction of template-containing calcium source micelle solution, multi-component crosslinking and gelation, confined hydrothermal crystallization, and multi-stage post-treatment. The primary technical obstacle to be overcome by this process route is the inherent contradiction that the nucleophilic hydrolysis rate of transition metal alkoxides such as tetrabutyl titanate and aluminum isopropoxide is much higher than that of tetraethyl orthosilicate. If various precursors are directly mixed without differentiation, the transition metal centers will undergo rapid and uncontrollable hydrolysis upon encountering moisture, quickly detaching from the liquid phase to form amorphous particle precipitates of titanium dioxide or aluminum hydroxide, making it difficult to achieve a uniform distribution of heteroatoms at the molecular scale into the silicate lattice. To address this, this invention introduces acetylacetone as a complexing rate-controlling agent. Through its keto-enol tautomerism, it undergoes an exothermic chelation reaction with the titanium and aluminum metal centers, constructing a high-density six-membered ring chelate steric barrier layer around the metal coordination inner layer. This flexible molecular-level barrier significantly reduces the probability of water molecules approaching and replacing the metal centers, thereby significantly suppressing the effective hydrolysis rate of the transition metal precursor, making it more coordinated with the hydrolysis and polycondensation of tetraethyl orthosilicate. It should be noted that the complexation protection of acetylacetone is a kinetic deceleration rather than an absolute shield. With the combined use of slow addition and acidic media to control the polycondensation rate, the system can gradually condense in a controlled manner, generating a composite sol with a silicon-oxygen framework as the main component and containing silicon-oxygen titanium and silicon-oxygen aluminum bridging oxygen links. This maximally suppresses the independent phase formation of the transition metal, laying a uniform precursor foundation for the subsequent hydrothermal stage where multiple elements co-enter the hard silica-calcium lattice. Based on this, by introducing block copolymers as soft templates to regulate the mesoporous structure and growth interface of the product, and by combining them with precise low-pressure hydrothermal conditions, mesoporous nanocrystals with high purity, high surface activity and large aspect ratio can be synthesized.
[0025] Before conducting performance evaluation, the test methods and characterization techniques involved in this specification are defined uniformly. The phase purity of the strength stabilizer itself is determined using X-ray powder diffraction, with copper target Kα rays as the radiation source, and a scanning range of 5° to 70°. The obtained diffraction patterns are compared with standard cards for hard silica and shale silica, and the relative content of each crystalline phase and the phase purity of the target phase are estimated using the reference intensity method. Furthermore, full-spectrum fitting is used for refinement to obtain changes in unit cell parameters before and after doping. A comparison of the X-ray powder diffraction patterns of representative strength stabilizer samples is shown below. Figure 1All samples in the examples exhibited sharp diffraction peaks characteristic of calcareous silica with straight baselines. Furthermore, no diffraction peaks belonging to an independent titanium dioxide phase were observed at approximately 25.3° 2θ, where the strongest characteristic peak of anatase titanium dioxide is located, or approximately 27.4° 2θ, where the strongest characteristic peak of rutile titanium dioxide is located. The area around approximately 25.3° 2θ is a clean region where neither the characteristic peaks of calcareous silica nor wollastonite are observed, and it is unaffected by the diffraction peaks of the aforementioned silicate phases. Therefore, the interpretation results are reliable. This confirms that titanium did not precipitate as an independent titanium dioxide phase, but rather entered the calcareous silica lattice as a dopant. In contrast, the comparative sample, which omitted the complexation rate control step, exhibited a significant amorphous dispersion background and a substantial decrease in the intensity of the characteristic diffraction peaks of calcareous silica. The microstructure, aspect ratio, and mesoporous structure of the crystals were observed using field emission scanning electron microscopy and transmission electron microscopy. The occupancy, distribution, and coordination state of heteroatoms in the crystal lattice were determined by combining atomic-level lattice images from high-resolution transmission electron microscopy, elemental distribution from energy dispersive spectroscopy (EDS), solid-state nuclear magnetic resonance (NMR), and X-ray photoelectron spectroscopy. The substitution and intercalation of aluminum and phosphorus in the silicon-oxygen tetrahedral framework were mainly supported by changes in the chemical shifts and binding energies of silicon, aluminum, and phosphorus-related nuclei from solid-state NMR. The preferential occupation of titanium in the interlayer spaces and defect sites of calcium-oxygen polyhedra was inferred by combining changes in interlayer contrast in high-resolution lattice images, the distribution of titanium along the interlayer in EDS, and the binding energy characteristics of titanium. The specific surface area and pore size distribution of the powder were determined based on nitrogen adsorption-desorption isotherms and using appropriate specific surface area calculation models and pore size analysis models. To characterize the effect of doping on phase transition stability, variable-temperature in-situ X-ray diffraction was used to perform programmed temperature scanning on the samples. The phase transition initiation temperatures corresponding to the weakening of the characteristic diffraction peaks of hard silicate and the appearance of characteristic peaks of high-temperature phases such as wollastonite were recorded. This was used to measure the shift of the critical point of phase transition instability temperature.
[0026] The mechanical and sealing performance evaluation of cement stone was conducted in accordance with the prevailing standards in the oil and gas well cementing industry. The base slurry used in the tests used API G-grade oil well cement as the matrix, with 35% silica sand added by weight of the base cement to form a conventional sand-added high-temperature resistant system. The silica sand was a coarse-fine two-graded silica sand composed of coarse silica sand and fine silica powder at a mass ratio of approximately 7:3, with a water-cement ratio of 0.44. A strength stabilizer was directly dry-mixed into the aforementioned dry cement at a certain proportion by weight of the base cement. The preparation, thickening time determination, and evaluation of free fluid and rheological properties of the cement slurry were conducted according to relevant standards for cementing tests in the oil and gas industry and API recommended practices. The thickening test was performed on a pressurized thickener simulating bottom hole circulation temperature and pressure. During curing, the cement slurry was injected into a standard mold and placed in a high-temperature, high-pressure curing vessel, and cured at 240 ℃ and 50 MPa under simulated ultra-high temperature deep well conditions for 14 days, 30 days, 90 days, and 180 days, respectively. After reaching the set age, the samples were removed. Compressive strength was determined on a pressure testing machine according to the relevant methods for testing the strength of cement mortar. Elastic modulus was calculated using the initial linear segment of the stress-strain curve. Water permeability of the cement stone was determined using the steady-state liquid method on a core displacement device, while porosity was determined comprehensively using a combination of saturated weighing and mercury intrusion porosimetry. Water loss was measured using an API-recommended high-temperature, high-pressure water loss meter under appropriate temperature and pressure conditions. The arithmetic mean of three parallel samples was used for each set of data to mitigate random fluctuations caused by variations in the preparation of a single sample.
[0027] Example 1
[0028] In this embodiment, 1 mol of tetraethyl orthosilicate is used as the measurement standard for the skeletal silicon source. Based on this, the amount of other components to be added is calculated, with the goal of preparing a strength stabilizer powder of about 100 grams.
[0029] The preparation process of the titanium-aluminum coordination precursor solution is as follows: 80 mL of anhydrous ethanol was added to a three-necked flask equipped with a magnetic stirrer, oil bath temperature control, a spherical reflux condenser, and inert gas micro-positive pressure protection. While stirring, 0.04 mol of aluminum isopropoxide and 0.04 mol of tetrabutyl titanate were accurately weighed and added sequentially to ensure that the molar ratio of aluminum to silicon and the molar ratio of titanium to silicon were both 0.04. The stirring speed was set to 400 r / min, and acetylacetone was added dropwise to the system over approximately 15 min via a constant-pressure dropping funnel. The amount of acetylacetone added was strictly controlled according to a 2.2:1 ratio of its molar amount to the total molar number of titanium and aluminum transition metal atoms to ensure that all highly active metal sites were chelated and coated. After the addition was complete, the oil bath was heated to 65 °C and stirred at a constant temperature under reflux for 2.5 h. The slight turbidity caused by trace hydrolysis in the early stage gradually disappeared, and the system eventually turned into a clear, transparent, bright yellow homogeneous liquid. It was cooled to room temperature, sealed and stored for later use, and denoted as solution A.
[0030] The preparation process of the silicon-phosphorus cocondensation sol is as follows: In another clean reactor, 150 mL of anhydrous ethanol was added as a dispersion medium, followed by the sequential addition of 1 mol of tetraethyl orthosilicate and 0.02 mol of triethyl phosphate, resulting in a phosphorus to aluminum molar ratio of 0.5. Subsequently, deionized water was added to the system at a water to tetraethyl orthosilicate molar ratio of 4.5:1, and dilute nitric acid was added dropwise to adjust and stabilize the pH of the system between 2.5 and 3.0. The system was then subjected to vigorous stirring at 600 r / min at room temperature for approximately 3.5 h for hydrolysis and aging, until tetraethyl orthosilicate was fully hydrolyzed and condensed, forming a clear, transparent, and viscous silicon-oxygen oligomer sol. During this stage, the hydrolysis of triethyl phosphate was relatively slow, and it was mainly uniformly dispersed in the silicon-oxygen oligomer sol at the molecular level, forming a transparent homogeneous system with the silicon-oxygen oligomers, denoted as solution B.
[0031] The preparation process of the template-containing calcium source micelle solution is as follows: 0.957 mol of calcium nitrate tetrahydrate was dissolved in 500 mL of deionized water. This amount of feed resulted in a molar ratio of calcium atoms to the total amount of the four framework elements (silicon, aluminum, titanium, and phosphorus) (1 + 0.04 + 0.04 + 0.02 = 1.10 mol) of approximately 0.87, falling within the target range of silicon-rich and calcium-poor. The molar number of the framework elements was calculated based on the molar number of the corresponding central atoms (silicon, aluminum, titanium, and phosphorus) in the added precursor. 12.0 g of Pluronic F127, a block copolymer with a number-average molecular weight of approximately 12600, was slowly added to the calcium salt solution as a soft template agent, resulting in a concentration of approximately 24 g / L in the solution, which is higher than the critical micelle concentration of the copolymer and sufficient to form a large number of micelles in the solution. The temperature was raised to 45 °C and continuously stirred at a medium speed for about 4 h to allow the copolymer to be fully dispersed and self-assembled to form isotropic micelles, resulting in a homogeneous micelle solution, denoted as solution C. The micelle solution is used as a soft template in subsequent processes to introduce mesopores into the product and regulate the crystal growth interface.
[0032] The multi-component crosslinking and gelation process is as follows. Solution A, cooled to room temperature, was placed in a high-precision syringe pump and added dropwise to solution B at a slow rate of approximately 2 mL / min, while simultaneously being ultrasonically stirred for about 1.5 h. The slow dropwise addition, in synergy with the acidic medium, allowed the titanium and aluminum centers, protected by acetylacetone complexation, to participate in condensation at a controlled rate, gradually forming a composite sol containing titanium silicate and aluminum silicate bridges with oxygen. During this process, the complexation protection of acetylacetone inhibited the rapid hydrolysis and polymerization of the transition metals, maintaining a transparent and homogeneous phase without independent phase precipitation. Subsequently, this homogeneous composite sol was injected into solution C containing micelles at the same slow rate, and the rotation speed was increased to 800 r / min to generate strong shear, ensuring uniform mixing at the molecular scale. At this point, the active silica species in the sol came into contact with calcium ions and reacted rapidly. After the components were mixed, the pH of the system was immediately adjusted with a 25% (w / w) tetramethylammonium hydroxide aqueous solution to raise and maintain the final pH value between 11.5 and 11.8. It should be noted that during the pH increase, calcium ions in the system did not exist in a free form, but rather rapidly combined with active silica species as the alkalinity increased, becoming immobilized in the calcium silicate gel network to form hydrated calcium silicate precursors. This avoided the formation of large amounts of macroscopic calcium hydroxide precipitates under strong alkalinity due to free calcium ions. To further ensure uniform calcium immobilization and suppress excessively high local alkalinity, the alkalinity adjustment process was carried out slowly under strong stirring. Tetramethylammonium hydroxide was chosen because it provides the necessary strongly alkaline mineralization environment for the formation of the hard calcium silicate double-chain structure, without introducing alkali metal impurities into the system like sodium hydroxide or potassium hydroxide. After pH adjustment, the high-alkalinity slurry was aged in a sealed container at room temperature with continuous stirring for 12 hours, allowing the calcium silicate gel to fully adsorb and assemble at the hydrophilic interface of the template agent, resulting in a uniform and highly reactive white gel slurry. Considering that the slurry still contains anhydrous ethanol from the precursor liquid and sol, as well as alcohols released from the hydrolysis of the precursor, in order to avoid excessively high vapor pressure of alcohols in the subsequent high-temperature closed environment and to ensure that the pressure system inside the reactor is mainly aqueous, the aged slurry is first subjected to reduced pressure rotary evaporation at 55 ℃ to 65 ℃ to remove most of the low-boiling-point alcohols before loading into the reactor. Then, deionized water is added to re-slurry and disperse it into an aqueous slurry with appropriate solid content, so that the system entering the reactor is basically an aqueous slurry.
[0033] The confined hydrothermal crystallization process is as follows: The white aqueous gel slurry, after being de-alcoholized and redispersed, is transferred to a self-sealing high-pressure reactor with a polytetrafluoroethylene liner. The filling degree of the gel slurry is controlled between 65% and 70% to maintain an appropriate gas phase space within the reactor, preventing overpressure caused by thermal expansion of the liquid in a full-liquid state, while also preventing excessive water from escaping into the gas phase due to an excessively large gas phase space. After sealing the reactor, it is placed in a programmable temperature-controlled oven and gradually heated to the target hydrothermal temperature of 220℃ at an initial heating rate of 1.5℃ / min, allowing the precursor to undergo a uniform and gentle crystal nucleation process. Since the low-boiling alcohols in the slurry have been largely removed in the previous de-alcoholization step, the system is mainly aqueous. At this filling degree, the pressure inside the reactor when the system reaches gas-liquid equilibrium at 220℃ is mainly determined by the saturated vapor pressure of water at this temperature, approximately 2.3 to 2.5 MPa, forming a stable high-temperature self-generated pressure environment. Crystallization is then carried out at this temperature-pressure boundary for 16 h. During this period, the amorphous gel network gradually undergoes dissolution and in-situ reprecipitation. Phosphorus, previously dispersed at the molecular level in the precursor, and titanium, located in the interlayer and defect regions, are incorporated into the lattice along with the development of the calcareous silica double chains and polyhedral layers. Under the guidance of the template micelles and the one-dimensional growth habit of calcareous silica itself, multiple elements are deposited and grown regularly along the dominant crystal axis, eventually developing into a doped calcareous silica nano-interwoven crystalline phase with a high aspect ratio and abundant mesopores. After crystallization, the heat source is cut off, and the reactor is allowed to cool naturally to room temperature.
[0034] The post-processing procedure is as follows: The reactor is opened, and the mother liquor containing a large amount of suspended white crystals is discharged. The mixture is centrifuged at 8000 r / min for approximately 15 min to achieve solid-liquid separation. The supernatant containing unreacted ions, free nitrate ions, and template agent degradation residues is discarded. The resulting solid phase is transferred to a washing container, and hot deionized water at 80 ℃ is added for re-slurry dispersion. The mixture is then ultrasonically vibrated at 200 W for approximately 15 min. The thermal field and ultrasonic energy open the aggregation interface, desorb and wash out the remaining free acid radicals, unreacted ions, and template agent fragments degraded after high-temperature hydrothermal treatment within the mesopores. The mixture is centrifuged again. This hot ultrasonic washing step is repeated at least three times until the supernatant is neutral. Considering the characteristics of poly(ethylene oxide)-poly(propylene oxide) block copolymers, such as the hydrophilic segments being dehydrated in a high-temperature aqueous phase and not easily dissolved and removed by water, the product was subjected to two deep solvent displacement washes with anhydrous ethanol after water washing. This utilized ethanol's excellent solubility in this type of copolymer to thoroughly extract and remove stubborn organic residues adsorbed on the pore walls. Simultaneously, the lower surface tension of ethanol replaced the water within the mesopores, preventing capillary shrinkage stress caused by water loss during subsequent drying, which could lead to mesoporous structure collapse and powder agglomeration. Finally, the solid phase was placed in a vacuum drying oven and continuously de-devoured for 12 h at an absolute pressure below 0.01 MPa and a temperature of 105 °C. The resulting dried powder cake was then pulverized by airflow and passed through a 500-mesh sieve to obtain the strength stabilizer product of this embodiment, denoted as S1.
[0035] The strength stabilizer product S1 obtained in this embodiment was observed by field emission scanning electron microscopy, and its microstructure is as follows: Figure 2 As shown. By Figure 2 As can be seen, S1 is composed of a large number of fine needle-like and fibrous nanocrystals interwoven with each other. Each individual whisker exhibits a nanoscale lateral size and a high aspect ratio. The whiskers overlap and stack each other to form a fluffy and porous three-dimensional interwoven network. No coarse and isolated crystal clusters or dense and hard aggregates were observed in the field of view. The above morphology is consistent with the description of the aforementioned hard silica calcium stone preferentially growing along its double chain direction into high aspect ratio mesoporous nanofibers, and obtaining highly fluffy, high specific surface area ultrafine powder after deep solvent replacement drying with anhydrous ethanol.
[0036] Example 2
[0037] This embodiment examines the effect of the calcium skeleton molar ratio within a defined range on the product. Except for adjusting the amount of calcium nitrate tetrahydrate to 0.935 mol, reducing the molar ratio of calcium atoms to the total amount of silicon, aluminum, titanium, and phosphorus skeletons (1.10 mol) to the lower limit of the range of 0.85, the other raw material types, ratios, and all process parameters are consistent with those in Example 1. The resulting strength stabilizer product is denoted as S2.
[0038] Example 3
[0039] This embodiment examines the case where the molar ratio of the calcium skeleton is at the upper limit of the range. The amount of calcium nitrate tetrahydrate added was adjusted to 0.99 mol, so that the molar ratio of calcium atoms to the total amount of skeleton elements (1.10 mol) was raised to the upper limit of the range of 0.90. The other conditions were the same as in Example 1, and the resulting strength stabilizer product was designated as S3.
[0040] Example 4
[0041] This embodiment adjusts the hydrothermal crystallization temperature gradient based on Example 1 to investigate the effect of crystallization temperature on the degree of crystallization perfection of the product. The target temperature for confined hydrothermal crystallization was lowered from 220 ℃ to 210 ℃, and the equilibrium pressure spontaneously established by the system was slightly reduced accordingly. The isothermal crystallization time remained at 16 h, and the heating rate and all other parameters were consistent with those in Example 1. The resulting strength stabilizer product was designated as S4.
[0042] Example 5
[0043] This embodiment further increases the hydrothermal crystallization temperature range to investigate the effect of the temperature-time coupling window on the product. The target temperature for confined hydrothermal crystallization was increased to 230 °C, and the isothermal crystallization time was correspondingly shortened to 14 h. All other conditions were the same as in Example 1, and the resulting strength stabilizer product was designated as S5. This embodiment shows that, with an appropriate shortening of the isothermal time, a well-developed product without obvious template carbonization can still be obtained at 230 °C. This indicates that the upper temperature limit of the system is not an isolated critical point, but rather coupled with the crystallization time: as the temperature increases, the holding time must be shortened accordingly; otherwise, prolonged high temperatures will trigger carbonization and degradation of the template agent.
[0044] Comparative Example 1 This comparative example aims to examine the consequences of omitting the titanium dopant component in the system. No tetrabutyl titanate was added during the precursor solution preparation stage; instead, 0.04 mol of aluminum isopropoxide was used alone to complex with acetylacetone. The amount of acetylacetone was adjusted accordingly to a molar ratio of 2.2:1 to aluminum atoms. The system only formed aluminum-phosphorus dual doping without interlayer titanium anchoring components. All other raw material ratios and process steps were completely consistent with Example 1, and the resulting product was designated D1.
[0045] Comparative Example 2 This comparative example aims to examine the consequences of omitting the phosphorus dopant component in the system and thus losing the charge compensation for aluminum. Triethyl phosphate was not added during the preparation of the silica-phosphorus sol, correspondingly reducing the total amount of framework elements from 1.10 mol to 1.08 mol. To adhere to the single variable principle and maintain the molar ratio of calcium to total framework elements at 0.87, the amount of calcium nitrate tetrahydrate was simultaneously adjusted to 0.940 mol. This ensures that the only difference between this comparative example and Example 1 is the presence or absence of phosphorus; all other raw material ratios and process steps are completely consistent with Example 1. The resulting product is denoted as D2.
[0046] Comparative Example 3 This comparative example aims to examine the consequences of using a conventional direct mixing process, omitting the acetylacetone complexation rate control step. The types and amounts of precursors were the same as in Example 1, but acetylacetone was not added during the preparation process. Instead, aluminum isopropoxide and tetrabutyl titanate were directly mixed with silanol solution before subsequent hydrolysis and hydrothermal treatment. All other conditions remained unchanged, and the resulting product was designated D3.
[0047] Comparative Example 4 This comparative example represents the conventional technical solution of existing silicate cement with added sand, that is, no strength stabilizer as described in this invention is introduced into the cementing cement, and only API G grade oil well cement with 35% silica sand is added to form a benchmark sand-added system. It serves as a blank reference for evaluating the performance improvement of each embodiment and the comparative example, and is denoted as D4.
[0048] The application and evaluation methods are as follows. The strength stabilizer powders obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were dry-mixed into a base slurry composed of API G grade cement and 35% silica sand at a dosage of 3.0% of the base cement mass. Comparative Example 4 did not include any stabilizer. All cement slurries were prepared at a water-cement ratio of 0.44, mixed and sheared, and then poured into standard molds. After curing at 240℃ and 50 MPa to the corresponding age, their compressive strength, elastic modulus, water permeability, and porosity were measured according to the aforementioned test methods. The key performance test results of each group of samples at 14 days and 180 days are summarized in the table below.
[0049] Performance test results table
[0050] Note: The target phase purity column in the table above refers to the phase composition of the strength stabilizer powder itself. The blank sand-addition system does not involve an independent stabilizer phase, so it is not listed.
[0051] As can be seen from the data in the table above, in all embodiments incorporating the ternary co-doped strength stabilizer of this invention, the compressive strength of the cement stone, after 180 days of ultra-high temperature curing, not only did not decline, but also showed a continuous slight increase compared to the 14-day age. The 180-day compressive strength remained stable in the range of approximately 47 MPa to 51 MPa, the elastic modulus remained between 7.0 GPa and 7.6 GPa, the water permeability was suppressed to an extremely low level of 0.005 mD to 0.012 mD, and the porosity also remained stable at around 18%. In stark contrast, Comparative Example 4, representing a conventional sand-addition system, experienced a strength collapse after 30 days, with the 180-day compressive strength dropping sharply to 16.5 MPa, the elastic modulus decreasing to 3.1 GPa, the water permeability deteriorating drastically to 0.48 mD, and the porosity climbing to 38.6%. Based on the 180-day compressive strength, Example 1 showed a relative improvement of more than two times compared to the blank control, while the water permeability decreased by nearly two orders of magnitude. This simultaneous leap in mechanical and sealing properties over a long period of time fully demonstrates the unexpected technical effects brought about by the present invention.
[0052] To clarify the microstructural reasons behind the aforementioned differences in macroscopic performance, the morphology, grain size, and phase transformation behavior of representative samples were further characterized. Scanning electron microscopy and transmission electron microscopy observations showed that the cement stone with the stabilizer from Example 1 maintained a dense network of interwoven fine needle-like whiskers after 180 days of curing, without any obvious isolated coarse crystal clusters. The grain size of the hard silicate, estimated using diffraction peak widths, increased only slowly from approximately 35 nm to approximately 40 nm between 14 and 180 days, a limited increase, indicating that the crystal coarsening caused by Oswald curing was effectively suppressed. In contrast, in Comparative Example 4 (blank with added sand), the grain size significantly coarsened from approximately 35 nm to hundreds of nanometers or even micrometers within the same period, and the network degenerated from a dense interwoven network to isolated coarse needle clusters, consistent with its macroscopic manifestations of strength collapse and pore coarsening. High-resolution lattice imaging and energy dispersive spectroscopy (EDS) results showed that titanium in the doped sample was mainly distributed along the interlayer of the calcium-oxygen polyhedron and enriched in the defect region. No obvious independent titanium dioxide phase diffraction peaks were observed. This, along with the binding energy characteristics of titanium in the X-ray photoelectron spectroscopy, supports the conclusion that titanium preferentially occupies the interlayer gaps and defect sites. The variable-temperature in-situ X-ray diffraction comparison results of the sample in Example 1 and the sample in Comparative Example 1 are shown below. Figure 3 .like Figure 3As shown, with increasing temperature, the titanium-free Comparative Example 1 sample exhibited a phase transition initiation signal earlier, showing a weakening of the characteristic diffraction peaks of hard silicate and the appearance of characteristic diffraction peaks of high-temperature phases such as wollastonite. In contrast, the ternary co-doped Example 1 sample showed a significantly higher phase transition initiation temperature, with the phase transition delayed to a higher temperature region. Therefore, at the simulated service temperature, Example 1 sample maintained the structural stability of the hard silicate phase, quantitatively reflecting the effect of titanium's interlayer pinning on shifting the critical point of phase transition instability. The cell parameters obtained from full-spectrum fitting also showed a regular change after doping, consistent with the entry of aluminum and phosphorus into the framework and titanium into the interlayer phase. This microscopic evidence provides direct experimental support for the two mechanisms proposed in this invention: suppressing crystal coarsening and delaying high-temperature phase transitions.
[0053] Within each embodiment, the gradient changes in parameters also exhibit a clear and predictable pattern. The only difference between Embodiments 1, 2, and 3 is that the molar ratio of the calcium skeleton is 0.87, 0.85, and 0.90, respectively. The performance of the three embodiments is similar and at an excellent level, indicating that within the limited range of 0.85 to 0.90, the system maintains a silicon-rich and calcium-poor thermodynamic environment, which can stably repel the secondary phase and generate high-purity hard calcium silicate, thus confirming the rationality of the limited ratio range. Examples 1, 4, and 5, which focus on the hydrothermal crystallization temperature, show a clear temperature dependence: when the crystallization temperature is lowered from 220 °C to 210 °C, the target phase purity of Example 4 decreases from 98.7% to 95.3%, the 180-day compressive strength also decreases accordingly, and the water permeability increases. This is because the driving force of dissolution-reprecipitation is insufficient at lower temperatures, a certain proportion of amorphous components remain in the gel network, and the mesoporous crystals are not fully developed. When the crystallization temperature is raised to 230 °C, the various indicators of Example 5 are basically equivalent to those of Example 1 at 220 °C, indicating that a well-developed product can still be obtained by appropriately shortening the isothermal time within a range slightly above 220 °C. However, considering that further increases in temperature will bring the risk of premature carbonization and degradation of the template agent and increase energy consumption, 220 °C combined with 16 h is still the preferred condition that balances crystallization quality and process economy.
[0054] The deterioration of the performance of each comparative example powerfully demonstrates the necessity of the technical features of this invention from the opposite perspective. It is necessary to first clarify the main controlling factor of early strength: at 14 days, the strength of cement stone mainly depends on the presence of successfully synthesized seed crystals in the system to exert a heterogeneous nucleation induction effect, and is not sensitive to whether all three doping elements are present. After removing titanium from Comparative Example 1 and phosphorus from Comparative Example 2, the system can still synthesize aluminum-phosphorus or aluminum-titanium-doped hard silica-calcium stone seed crystals through complexation rate control and hydrothermal crystallization. Therefore, the 14-day strengths of the two examples (45.6 MPa, 44.8 MPa) are close to those of the examples (45.9 MPa to 46.8 MPa), consistently reflecting the dominant role of seed nucleation induction ability in the early stage. However, after reaching a long age, Comparative Example 1, lacking the restraint of interlayer titanium rivets, suffered from uncontrolled grain boundary slip and phase transformation instability of hard silicate under continuous thermal stress at 240 °C. Its 180-day compressive strength dropped to 38.4 MPa, and its water permeability increased to 0.068 mD, indicating that the titanium component plays an irreplaceable role in suppressing high-temperature phase transformation and maintaining long-term stability. Comparative Example 2, after phosphorus removal, showed a more severe situation. Due to the loss of compensation for aluminum negative charge defects and the release of lattice expansion stress, the localized distortion induced by aluminum doping became preferential depolymerization sites at high temperatures. Furthermore, the charge imbalance weakened lattice stability, further reducing its 180-day compressive strength to 35.1 MPa, and the target phase purity also declined to 93.6%. This demonstrates that the charge and stress compensation effects of phosphorus are prerequisites for aluminum doping to truly exert its strengthening effect; both must coexist. In Comparative Example 3, omitting the acetylacetone complexation rate-control step resulted in uncontrolled rapid hydrolysis of titanium and aluminum alkoxides during direct mixing. A large amount of transition metal failed to enter the silicate lattice and precipitated as amorphous titanium dioxide and aluminum hydroxide, causing the target phase purity to plummet to 81.4% (e.g., ...). Figure 1 As shown, the diffraction pattern of Comparative Example 3 exhibits a significant amorphous dispersed background and a greatly weakened characteristic diffraction peak of hard silicate (calcium silicate). The doping is ineffective; in reality, no seed crystal with effective nucleation and anti-deterioration functions was synthesized. Therefore, its behavior degenerates to that of a blank-addition system. The 14-day strength (42.8 MPa) is basically equivalent to the blank control (42.5 MPa), only slightly higher due to the weak filling and sporadic nucleation effect of the residual amorphous components. However, significant strength degradation occurs over long-term, decreasing to 19.5 MPa at 180 days, and water permeability deteriorates to 0.42 mD, consistent with the degradation trend of the blank control. The results of Comparative Example 3 clearly demonstrate that the complexation rate control process is the decisive step for successful seed crystal synthesis. Once this step is missing, even with all three doping elements, no effective strength stabilization effect can be obtained.
[0055] Based on the data from various groups, it can be concluded that the strength stabilizer of this invention achieves constant strength and a leap in sealing performance under ultra-high temperature and long-term curing conditions due to the synergistic superposition of multiple mechanisms rather than the simple effect of a single component. In the early stage of curing, a large number of uniformly distributed nanocrystals, with their extremely low crystallization potential barrier, lower the nucleation energy barrier of the system to near zero. Supersaturated silicate ions and free calcium ions are rapidly adsorbed by the active interface of the crystals, resulting in the explosive epitaxial growth of a massive number of micro whiskers within an extremely narrow time window. The simultaneous growth of numerous crystals depletes the reactants, fundamentally cutting off any Oswald curing path by which any single crystal grows into a coarse mass by absorbing surrounding materials. This permanently freezes the microstructure of the cement stone in a highly dense, nanoscale interwoven three-dimensional network, which is the morphological basis for the significant reduction in porosity and permeability. Meanwhile, within the whiskers, aluminum-phosphorus co-doping, by raising the activation energy of silicon-oxygen bond breaking and compensating for some charge and stress, suppresses the high-temperature depolymerization pathway of silicate double chains at the molecular bond energy level. Titanium atoms, primarily acting as interlayer rigid rivets, pin the slip path of atomic layers, delaying the phase transition instability temperature beyond the service temperature range. The former protects the intrinsic bond strength of the whiskers, while the latter protects the topological stability of the framework. The densely interwoven network dissipates external thermal stress layer by layer through frictional sliding and pull-out work between whiskers. It is precisely the mutual interaction and support of these three effects—morphological freezing, bond energy strengthening, and phase transition pinning—within the same material system that allows each embodiment to maintain its strength or even slightly increase it under extreme temperature and pressure testing for up to 180 days. In contrast, any comparative embodiment, lacking any one of these elements, inevitably experiences varying degrees of performance decline over long-term use. This, from both positive and negative perspectives, verifies the completeness of the technical solution of this invention and the indispensability of each component.
[0056] The embodiments described above are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-temperature cement stone strength stabilizer based on crystal phase stabilization, characterized in that, The stabilizer contains mesoporous nano-hard silicate calcium crystal seeds co-doped with aluminum, phosphorus, and titanium. The preparation method of ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization includes the following steps: S1. Disperse aluminum source and titanium source in organic solvent, add complexing agent to carry out chelation reaction to obtain precursor solution A; S2. Disperse the silicon source and phosphorus source in an organic solvent, add water and an acid regulator to carry out a hydrolysis and polycondensation reaction to obtain silicon-phosphorus co-condensation sol B; S3. Dissolve the calcium source in water, add the block copolymer template agent, and mix to obtain micelle solution C; S4. The precursor solution A is added to the silicon-phosphorus cocondensation sol B and mixed to obtain a composite homogeneous sol. Then, the composite homogeneous sol is injected into the micelle solution C, and an alkaline regulator is added to adjust the pH value of the mixture. After sealed aging, a gel slurry is obtained. S5. The gel slurry is subjected to a descaling treatment to remove the organic solvents and alcohols released by the hydrolysis of the precursor, and water is added to redisperse the mixture to obtain an aqueous gel slurry with water as the main liquid medium. S6. The aqueous gel slurry is placed in a closed reactor for hydrothermal crystallization reaction; S7. After the hydrothermal crystallization reaction is completed, the product is separated, washed, solvent replaced and dried to obtain the ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization. In step S1, the organic solvent is anhydrous ethanol, the aluminum source is aluminum isopropoxide, the titanium source is tetrabutyl titanate, the complexing agent is acetylacetone, and the ratio of the number of moles of the complexing agent to the sum of the number of moles of titanium atoms in the titanium source and aluminum atoms in the aluminum source is 2.2:
1. In step S2, the silicon source is tetraethyl orthosilicate, and the phosphorus source is triethyl phosphate; in the hydrolysis-condensation reaction, the molar ratio of water to tetraethyl orthosilicate is 4.5:1; the acid regulator is nitric acid, and the addition of the acid regulator controls the pH value of the reaction system to be between 2.5 and 3.
0.
2. The ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization according to claim 1, characterized in that, In the stabilizer, the molar ratio of phosphorus to aluminum is 0.5; the total molar ratio of calcium to the framework elements silicon, aluminum, titanium and phosphorus is 0.85 to 0.
90.
3. The ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization according to claim 1, characterized in that, In the microcrystalline structure of the stabilizer, aluminum atoms replace silicon atoms in the silicon-oxygen tetrahedral framework, phosphorus atoms are embedded in the silicon-oxygen tetrahedral framework to partially compensate for the negative charge vacancies of the aluminum atoms, and titanium atoms are located in the interlayer gaps of the calcium-oxygen polyhedral layers of the hard silicate.
4. A method for preparing an ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization as described in any one of claims 1 to 3, characterized in that: In step S3, the calcium source is calcium nitrate tetrahydrate, and the block copolymer template agent is Pluronic F127; the preparation process of the micelle solution C includes heating the mixture to 45 °C and continuously stirring until the block copolymer template agent is completely dispersed to obtain a homogeneous micelle solution.
5. The preparation method of the ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization according to claim 4, characterized in that, In step S4, the alkaline regulator is an aqueous solution of tetramethylammonium hydroxide; the alkaline regulator is added to adjust the pH value of the mixed system to be constant between 11.5 and 11.8; the sealed aging time is 12 h.
6. The preparation method of the ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization according to claim 4, characterized in that, In step S6, the filling degree of the aqueous gel slurry in the sealed reactor is controlled between 65% and 70%; the initial heating rate of the hydrothermal crystallization reaction is 1.5 ℃ / min, the target hydrothermal temperature is 220 ℃, and the isothermal crystallization time at 220 ℃ is 16 h.
7. The preparation method of the ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization according to claim 4, characterized in that, In step S7, the washing includes ultrasonic washing with deionized water at 80 °C at least 3 times; the solvent replacement is deep solvent replacement using anhydrous ethanol; and the drying process is continuous de-vaporization drying for 12 h under conditions of absolute pressure less than 0.01 MPa and temperature of 105 °C.
8. The preparation method of the ultra-high temperature cement stone strength stabilizer based on crystal phase stabilization according to claim 4, characterized in that, In step S5, the removal process involves vacuum distillation of the gel slurry at 55°C to 65°C to remove organic solvents and alcohols.
Citation Information
Patent Citations
Oil well cement high-temperature strength stabilizer and cement paste for well cementation, and preparation method of cement paste
CN112830700A
Method for regulating and controlling distribution of silicon and aluminum in molecular sieve framework and product thereof
CN116924426A